Seeing various adventures through a mirror: Detecting translator's stylistic visibility in Chinese translations of Alice's Adventure in Wonderland. - Fang, Yu; Liu, Haitao (Digital Scholarship in the Humanities, 2023)
The visibility of translator's style is a much-discussed topic in translation studies with the application of corpus tools. So far, however, no agreement has been reached. The present study aims to explore this issue by a comparison of three Chinese translations of the English literary work, Alice's Adventure in Wonderland , using two stylometric techniques, bootstrap consensus tree analyses, and bootstrap consensus network analyses. The results show that all the three Chinese translations preserved the style of the original text and that individual translator's style could not be identified based on the entire set of part-of-speech (POS) tags. Furthermore, a feature selection method (the chi-square metric) was used to obtain the top fifteen distinctive POS unigrams and bigrams, and these distinctive features successfully identified translatorial fingerprints across the three translations examined. The findings suggest that translators have their own stylistic choices when translating the same text, but their stylistic differences can only be detected by distinctive features. Our attempt to combine feature selection methods and stylometric techniques may offer new insights into the investigation of translator's stylistic visibility in translation studies.